Grado de confiabilidad de las pruebas de Tamizaje PAP e IVAA en comparación con las Muestras Anatomopatológicas - biopsia, para la Identificación de lesiones precancerosas del Cuello uterino en mujeres en edad fértil Atendidas en el consultorio de prevención de Cáncer de cuello uterino, Hospital Amazónico - Pucallpa, Enero 2013 – Diciembre 2014 - Bocanegra Flores, Karen Andrea (2015)
This research is a comparative descriptive cross-sectional study, conducted with the Aim of determining the degree of reliability of Pap screening tests and Visual Inspection with Acetic Acid versus pathological specimens - biopsy for identifying Precancerous lesions cervix in women of childbearing age who were treated at the Clinic for the prevention of cervical cancer, the Amazon Hospital - Pucallpa; during The period January 2013 to December 2014. The study population consisted of 81 Women of childbearing age, which shows the complied 100% of the population. Data Collection was conducted by reviewing the records of PAP, VIA biopsy and medical Records, which were processed through SPSS version 22 chi2 Pearson. The conclusions were: the risk factors associated with intraepithelial lesions with Respect to age are between 31-45 years old, who have started their first sexual Relationship between 12 to 19 years in the number of sexual partners of 3 and Average parity 3 children. With respect to the PAP were 50.6% with LSIL, 12.3% with HSIL and 37% were negative; VIA while 70.4% were positive, negative 22.2% and 7.4% (6) they resulted in suspected cancer. In turn biopsy results were obtained Being 54.3% of women were found to have CIN I; followed by CIN II 23.5% and 8.6% Of women in the study had a score of carcinoma in situ. Also 13.6% were negative Cases. When comparing the results of biopsy PAP PAP 47 true positive cases were Obtained false positive PAP four cases, false negative PAP and finally 23 cases 7 Cases of true negatives of the PAP. Meanwhile biopsy results comparing the VIA 55 VIA true positive cases false positive VIA 8 cases, false negative cases and finally VIA 3 15 true negative cases was obtained the VIA. Concluding that: the degree of Reliability of PAP is significant at 5%, that is reliable to 95% (X 2 = 42.683, p <0.05; in This case p = 0.000); VIA otherwise, who does not keep a reliability of 95% (X 2 = 3,601 and if p <0.05, in this case p = 0.722)